Analysis and modification of blue sapphires from Rwanda by ion beam techniques - D. Bootkul (2018)
© 2015 Elsevier B.V. Blue sapphire is categorised in a corundum (Al 2 O 3 ) group. The gems of this group are always amazed by their beauties and thus having high value. In this study, blue sapphires from Rwanda, recently came to Thai gemstone industry, are chosen for investigations. On one hand, we have applied Particle Induced X-ray Emission (PIXE), which is a highly sensitive and precise analytical technique that can be used to identify and quantify trace elements, for chemical analysis of the sapphires. Here we have found that the major element of blue sapphires from Rwanda is Al with trace elements such as Fe, Ti, Cr, Ga and Mg as are commonly found in normal blue sapphire. On the other hand, we have applied low and medium ion implantations for color improvement of the sapphire. It seems that a high amount of energy transferring during cascade collisions have altered the gems properties. We have clearly seen that the blue color of the sapphires have been intensified after nitrogen ion bombardment. In addition, the gems were also having more transparent and luster. The UV-Vis-NIR measurement detected the modification of their absorption properties, implying of the blue color increasing. Here the mechanism of these modifications is postulated and reported. In any point of view, the bombardment by using nitrogen ion beam is a promising technique for quality improvement of the blue sapphire from Rwanda.